Peran Administrasi Kesiswaan Dalam Pengenalan Lingkungan Sekolah di SD IT Future Islamic School - Aliza Aliza; Annisa Damai Yanti Samoeri; Melisa Putri; Nailah Assahira; Rima Junita Putri; Sakban Sakban (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Administration is very necessary for the continuity of the teaching and learning process in the world of education. All of that cannot be separated from the activeness of those who master the administration in the school. People often underestimate the field of administration, even though if the administration is held by less skilled people then the administration will be messy and will not run properly. People who hold administration are people who have been trained in their field (people who have received knowledge or training). Administration is not only in financial terms but also in our neatness and order in bookkeeping. Administration is not only carried out within a certain time but every day systematically. The success of education in schools must be supported by orderly, directed, and planned school administration services. Where in its implementation must follow the direction of the development of an increasingly modern era and growing technological media. For this reason, there needs to be a clear and programmatic division of administrative tasks in each school to create a better school later.